Safeguarding Patient Care: The Intersection of Documentation and Legal Aspects in Health Care - Debraj Banik; Ravindra S. Honnungar; Perumal P.; Vinay S. Bannur (Indian Journal of Forensic Medicine and Pathology, 2025)
Introduction: Accurate, complete, and timely medical documentation is a cornerstone of safe and effective healthcare delivery. It ensures continuity of care, facilitates communication among healthcare providers, and serves as an essential medico-legal record. Inadequate or incomplete documentation can compromise patient safety, lead to diagnostic or therapeutic delays, and expose practitioners to legal liability. This study aims to assess the quality and completeness of inpatient medical records across multiple clinical departments in a tertiary care hospital and to examine the legal and ethical implications associated with documentation de𿿿ciencies. Materials and methods: A retrospective descriptive study was conducted in a 1250- bed multispecialty teaching hospital. Medical records from nine departments like Internal Medicine, Gynaecology & Obstetrics, Forensic Medicine & Toxicology, General Surgery, ENT, Ophthalmology, Paediatrics, Dermatology, and Psychiatry were evaluated. Using systematic random sampling, 50 inpatient case sheets were selected from each department, yielding a total sample of 450 records from April 2022 to April 2023. A structured 12-domain audit tool assessing demographics, admission details, history, examination 𿿿ndings, investigations, diagnosis, treatment notes, procedure-related entries, daily progress, discharge summaries, signatures, and supporting documents was used to analyze documentation completeness.Results: The audit revealed marked inter-departmental variation in documentation standards. Forensic Medicine & Toxicology demonstrated the highest accuracy, with only 1.1% cumulative documentation errors, reÁecting stringent medico-legal protocols. The highest de𿿿ciencies were observed in Internal Medicine (18.5%) and General Surgery (11.7%), largely involving incomplete demographic entries, irregular clinical notes, missing time documentation, and inconsistent 𿿿ling f supporting documents. Additional lapses were noted in operative notes, weekend entries, and signature authentication across several departments. Conclusion: Regular audits, training in medical record-keeping and implementation of standardized documentation protocols are essential to improve the quality of medical records and reduce medico-legal risks. Strengthening documentation practices supports better patient care, enhances institutional accountability, and safeguards healthcare professionals in legal contexts.